Modeling of Time of Arrival Method for Lightning Locating Systems - Saeed Vahabi-Mashak; Zulkurnain Abdul-Malek; Kamyar Mehranzamir; Hadi Nabipour-Afrouzi; Behnam Salimi; Chin-Leong Wooi (Advances in Meteorology)
Various methods are used to locate cloud-to-ground lightning flashes. Even though a higher cost is incurred, a network of sensor stations is preferable to a single station due to the improved accuracy. For a single station measuring system, the accuracy of its analyses is mostly based on the chosen mathematical equations which can be solved in either linear or nonlinear mode. The sensitivity of the measuring equipment used is also particularly significant. This paper concentrates on the modelling of time of arrival (TOA) technique for locating a lightning flash by utilizing three broadband antennas. Consequently, by employing the developed model, the influences of geometric parameters on the accuracy of the model are evaluated. Therefore, a Matlab based simulation of the measuring system is developed. In the developed codes, randomly located lightning flash with its corresponding electromagnetic radiation was modelled. Results show that parameters such as lightning path shape, distance of the leader, and leader location can directly affect the accuracy of the TOA technique for extracting the azimuth and elevation.